ADRESSING THE ABILITIES OF LANGUAGE LEARNERS (Ustozlar uchun, 2025)
This article examines the importance of addressing the diverse abilities of language learners in the process of foreign language education. It highlights key factors influencing learner abilities, including individual differences, motivation, learning styles, and prior linguistic knowledge. The study emphasizes the role of differentiated instruction, balanced development of language skills, and effective assessment practices in creating inclusive and learner-centered classrooms. By recognizing and responding to learners’ abilities, language teachers can enhance student engagement, improve learning outcomes, and foster lifelong language learning.